The world of the Indian Ocean, 1500-1800 :studies in economic, social, and cultural history - Pearson, M. N. (Variorum collected studies series, 2018)
The articles in The World of the Indian Ocean, 1500-1800 describe the activities of people living on the coasts of the Indian Ocean, generously defined, during the early modern period. Most are based, at least in part, on Portuguese materials. A broad theme linking them all is the claim that in most areas of society and economy early modern Europeans and Asians had much in common, with the newly arrived Europeans having no particular advantage over their Asian interlocutors. The first five studies discuss aspects of trade and commerce, while the next group deal with social and religious themes, including conversions and a much quoted early attempt to investigate 'littoral society'. The third section presents four discussions of aspects of the early contact between Indian and European medical systems.